Meuseuraya dan Perubahan Sosial Bertani di Gampong Ranto Panyang Barat Kecamatan Meureubo Kabupaten Aceh Barat - Dela Rahmadani; Maulia Asma; Aprilia Maulina; Nur Habibah; Idazufina Idazufina; Sopar Sopar (Jurnal Ilmu Sosial dan Humaniora, 2026)
This study aims to examine social changes in rice farming practices and the sustainability of the meuseuraya culture in Rantoe Panyang Barat Village, Meureubo District, West Aceh Regency, amidst the influx of modernity and agricultural digitalization. The method used was qualitative research with a descriptive approach through observation and interviews with farmers, traditional leaders, and agricultural machinery operators. The results indicate that meuseuraya, as a form of traditional mutual cooperation, has decreased in intensity due to the use of agricultural technology such as tractors and combine harvesters. This technology has a positive impact in terms of time and energy efficiency, but simultaneously reduces social interaction and solidarity among residents. Nevertheless, the values embodied in meuseuraya are still considered important by the community as a cultural identity and social unifier. Therefore, adaptation efforts are needed to ensure the meuseuraya tradition remains relevant in the context of modern agriculture.